The challenges of incorporating consumer reliability preferences into electricity markets with a capacity requirement - Frank A. Felder (The Oxford Institute for Energy Studies, 2024)
One objective of retail electricity markets is to enable end-use consumers to incorporate their reliability preferences into their purchasing decisions. This paper investigates if and how this can be done in electricity markets with a capacity requirement. It integrates the standard loss of load and cost minimization approach from the economic literature with probabilistic resource adequacy informed by the engineering literature for electricity markets with capacity requirements. For these electricity markets, a partial solution that allows retail consumers to opt out entirely or partially from capacity markets could help improve social welfare. This solution allows consumers to use their individual estimate of the cost of power outages based on the relevant outage characteristics instead of a system planner estimating a generic value of lost load. The goal of achieving optimal levels of reliability remains elusive, however, due to incomplete probabilistic reliability models, consumers' inability to opt out of capacity requirements, and transaction costs.
Keywords: 330; generation capacity requirements; load control; loss of load probability; price-responsive demand; reliability; resource adequacy; Transaction Costs